ECE661: Artificial Neural Network / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2014)
This course provides introductions to various aspects of artificial neural network, with emphasis on elements of design of trainable systems. Topics include linear and nonlinear neurons, multilayer networks, backpropagation algorithms, unsupervised learning algorithms, advanced neural network architectures and training algorithms. Theories and real world applications will be covered.